Analisis Pendapatan Usahatani Kentang Di Kecamatan Kabanjahe, Kabupaten Karo - Dian Hendrawan; Dedi Kusbiantoro; Khairunnisyah Nasution; Yenni Asbur; Nurhayati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Potatoes are the leading agricultural product in Kabanjahe itself. Under these conditions, Kabanjahe has great potential in terms of agriculture, especially potato plants. The size of a farm's income is influenced by revenue and production costs. However, currently potato farmers in Kabanjahe are faced with a problem, namely the productivity of potatoes that is not yet maximized and the price of potatoes is uncertain, which will affect the productivity and income earned by farmers. This study aims to analyze the income of potato farming. The research was conducted in August 2022. Data analysis used income analysis and R/C ratio analysis. The average income of potato farming in Kaban Village, Kabanjahe District, Karo Regency is Rp. Rp. 29,967,190/ha/MT. The average total cost incurred in potato farming activities is IDR 55,321,810/ha/MT, and the average income in potato farming is IDR 85,289,000/ha/MT. This means that potato farming in Kabanjahe District, Karo Regency is still profitable because farmers' income can still cover the total costs incurred during the production process of the potato farming business.